Improving Number Addition Operations and Social-Emotional Skills Through Creative Play in Early Childhood - Suci Castellia Ngangova Abdullah; Iva Sarifah; Yuliani Nurani (Green Publisher Indonesia, 2025)
This research is motivated by the importance of developing the ability to operate numbers, add and social-emotional skills in early childhood which is still not optimal. Initial observations at Bintang Kecil Kindergarten show that mathematics learning is still conventional and lacks integration of social-emotional aspects in the process. This class action research was carried out in two cycles with the research subjects of six children in group B. Each cycle consisted of planning, implementation, observation, and reflection stages. Data was collected through observation, documentation, and interviews with school principals, then analyzed qualitatively and quantitatively. The results showed a significant increase in the operation ability of the sum number from the average TCP of 21.5 (44.79%) in the first cycle to 37.5 (78.13%) in the second cycle. Social-emotional skills also increased from an average TCP of 21.5 (44.79%) to 37.33 (77.77%). Improvements were seen in all aspects measured, including understanding the concept of addition using money, the use of mathematical symbols, as well as self-expression and collaboration in play activities. The application of creative play methods has proven to be effective in improving both aspects of child development simultaneously. These findings imply the importance of an integrated learning approach that integrates cognitive and social-emotional development through meaningful play activities.